On the development of user adapted e-learning schemes for teachers - Tzouveli, Paraskevi K.; Tsapatsoulis, Nicolas; Kollias, Stefanos D.; Michaelidou, M. (My University, 2003)
In this paper we present an innovative distance-learning scheme that employs dynamic user evaluation both content as well as behavior based in order to allow for dynamic training that is adapted to the user. Through content-based evaluation the appropriate learner profile is selected, influencing the level and the contents of the offered courses while behavioral evaluation affects the pace of training and the way information is presented to the user. Learner profiles are created and continuously updated through an e-survey tool that is integrated to the system. In its current form the presented system aims at increasing the familiarity with ICT of teachers working in the Special Education sector.
Keywords: User adapted e-learning; E-surveys; E-evaluation; ICT level estimation